Rational Expectations and Short-Run Neutrality: A Reexamination of the Role of Anticipated Money Growth - Carns, Frederick; Lombra, Raymond (The Review of Economics and Statistics, 1983)
Frederick Carns, Raymond Lombra, Rational Expectations and Short-Run Neutrality: A Reexamination of the Role of Anticipated Money Growth, The Review of Economics and Statistics, Vol. 65, No. 4 (Nov., 1983), pp. 639-643